Emotion and cognition: on the cognitive processing model of nostalgia - Cao, Shurong (Frontiers in Psychology, 2024)
Nostalgia is a common emotional phenomenon, but its complexity has resulted in a limited understanding and interpretation. This study, grounded in emotional cognitive science, develops a cognitive processing model of nostalgia, encompassing its triggering mechanism, cognitive processes, and effects. The analysis indicates that nostalgia functions as an adaptive mechanism for individuals with deficiencies in belongingness and low-avoidance tendencies, helping them cope with disruptions in self-continuity by forging symbolic social bonds in a distant and idealized timespace.Essentially, nostalgia allows individuals to reconstruct alternate systems of meaning and value, which serve as references for defining self-worth and identity. This study advances the understanding of the complex cognitive processing involved in nostalgia and also provides an important reference for the study of complex emotions.